Specific features of professional moral qualities of cadets of the institutions of higher education of the Ministry of Internal Affairs of Ukraine - K. I. Maravska (Law and Safety)
The results of empirical research of professional moral qualities of cadets of the institutions of higher education of the Ministry of Internal Affairs of Ukraine in the context of specific features of their development have been considered. It has been emphasized that the problem of development of moral qualities of cadets is stipulated by the high level of requirements to general, professional and moral qualities of police officers, the need to take into account them within professional and psychological selection of candidates for the positions of police officers and to form them in the educational process in the institutions of higher education of the Ministry of Internal Affairs of Ukraine. This problem is complex, especially relevant in the context of the development of professional legal awareness and the culture of law enforcement officers at the stage of training in higher educational institutions.